Welfare Implications of Currency Integration: Labor Mobility and Pricing-to-Market. Issue 1 (2nd January 2016) - Yoshimi, Taiyo
Abstract: In this paper, we examine the welfare cost of renouncing monetary policy autonomy in a model that includes labor mobility and pricing-to-market (PTM) behavior in firms. We find that renouncing monetary policy autonomy becomes a cost of currency integration when the consumption basket weights differ between candidate countries and when country-specific total factor productivity (TFP) shocks hit economies, even when the union fulfills the classic optimum currency area theory of labor mobility. We also found that a firm's PTM behavior has a significant effect on the welfare implications of currency integration combined with labor mobility. For instance, currency integration does not produce greater welfare losses in the PTM case (where the labor input weights differ across member countries and asymmetric labor disutility shocks occur), although greater welfare losses arise in the case of producer currency pricing.